The Historical Background of Quality Assurance at Laboratório de Imagem Molecular of the Centro de Desenvolvimento da Tecnologia Nuclear - Alexandre Vilaça Silva; Rodrigo Modesto Gadelha Gontijo; Andrea Vidal Ferreira (Brazilian Journal of Radiation Sciences)
The Centro de Desenvolvimento da Tecnologia Nuclear has a small animals positron emission tomograph in its Laboratório de Imagem Molecular. This equipment, the GE HealthCare LabPET SOLO 4 model, is widely used in preclinical studies related to the development of new radiopharmaceuticals or novel applications of conventional radiopharmaceuticals. The “PET Image Quality” subproject, integrated into the Centro de Desenvolvimento da Tecnologia Nuclear multi-year planning for 2018-2022, proposed actions involving quality assurance and human resources development for the laboratory. This work aims to consolidate the historical trajectory of Quality Assurance at Laboratório de Imagem Molecular of the Centro de Desenvolvimento da Tecnologia Nuclear. A search for documents related to the laboratory was conducted in the institutional quality system, called d-Qualidade, while a search for the curricula vitae of laboratory researchers was performed on the Plataforma Lattes, with the purpose of identifying the main products generated related to the Quality theme in the laboratory. The scientific production of the laboratory team demonstrates its pioneering role in Brazil in developing studies about the Quality Management applied to the small animals positron emission tomogragh. The laboratory history in the field of Quality Management emphasizes its national prominence and reveals the group's commitment over the past decade to significant technical/scientific production.